Family social climate and self-concept in students of a state educational institution - Estrada Araoz, Edwin (2020)
Objective: to determine the relationship that exists between the family social climate and self-conceptin secondary education students of a state educational institution in El Triunfo. Methodology: theapproach was quantitative, the design was not experimental and the correlational level. The samplewas made up of 231 students from the secondary education level through a stratified probabilisticsampling to which the Moos and Trickett (1974) Scale of Family Social Climate (FES) and the Garcíay Musitu Scale AF-5 were applied. (1999). Results: it was found by Spearman’s rho test that thereis a direct and significant correlation between family social climate and self-concept (rho = 0.532; p<0.05). Likewise, a direct and significant correlation was found between the family social climate andthe dimensions of academic self-concept (rho = 0.459; p <0.05), social self-concept (rho = 0.343; p<0.05), emotional self-concept (rho = 0.552; p <0.05), family self-concept (rho = 0.444; p <0.05) andphysical self-concept (rho = 0.559; p <0.05). Conclusion: students who perceive an adequate familysocial climate could have a better self-concept.